2014
DOI: 10.3171/2014.5.jns132279
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of methylguanine methyltransferase promoter methylation in glioblastoma using dynamic contrast-enhanced magnetic resonance and diffusion tensor imaging

Abstract: Object The methylation status of the methylguanine methyltransferase (MGMT) promoter has been associated with treatment response in glioblastoma. The authors aimed to assess whether MGMT methylation status can be predicted by dynamic contrast-enhanced (DCE) MRI and diffusion tensor imaging (DTI). Methods This retrospective study included 43 patients with pathologically diagnosed glioblastoma who had undergone preoperative DCE-MRI and DTI and whose MGMT methylation status was available. The imaging features we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 16 publications
1
70
3
1
Order By: Relevance
“…A potential limitation of the present study is the sample size, which may limit the power of the statistical analysis, such that some interactions between DSC and DCE parameters may not have been detected. Another limitation is that due to the retrospective design of this study assessment of the DNA repair enzyme O 6 ‐methylguanine‐DNA methyltransferase (MGMT) promoter status was not available for most of the patients, so that we could not determine to what extent this prognostic parameter correlated to the MR perfusions parameters in this cohort . A further limitation is the retrospective design in itself, and our findings encourage the intraindividual comparison of DSC and DCE in larger prospective studies.…”
Section: Discussionmentioning
confidence: 92%
“…A potential limitation of the present study is the sample size, which may limit the power of the statistical analysis, such that some interactions between DSC and DCE parameters may not have been detected. Another limitation is that due to the retrospective design of this study assessment of the DNA repair enzyme O 6 ‐methylguanine‐DNA methyltransferase (MGMT) promoter status was not available for most of the patients, so that we could not determine to what extent this prognostic parameter correlated to the MR perfusions parameters in this cohort . A further limitation is the retrospective design in itself, and our findings encourage the intraindividual comparison of DSC and DCE in larger prospective studies.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies also illustrated relationships between imaging features and genomic tumor composition . Several prior studies have described distinctive radiological features of GBM with MGMT promoter methylation using conventional MRI, diffusion weighted imaging (DWI), and dynamic contrast‐enhanced MRI (DCE‐MRI), but there are also some discrepancies …”
Section: Discussionmentioning
confidence: 99%
“…86 A study of 43 GBM patients using DCE-MRIfound that MGMT methylated tumors had increased permeability (higher K trans ) compared to unmethylated tumors. 87 The same group also reported that the initial area under the time-to-signal intensity curve from DCE imaging stratifies survival in promoter unmethylated MGMT GBM, but not in methylated tumors. 89 Arecent study combined both structural and physiologic MR imaging to derive an accurate marker for MGMT promoter methylation status in 92 patients with GBM.…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 93%
“…85 Conversely, higher average ADC values are associated with MGMT promoter methylation. 86, 87 One study found higher rCBV in unmethylated versus methylated tumors, 88 although another study found no significant association. 86 A study of 43 GBM patients using DCE-MRIfound that MGMT methylated tumors had increased permeability (higher K trans ) compared to unmethylated tumors.…”
Section: Clinical Applications Of Advanced Mrimentioning
confidence: 99%